Hemoptysis: Beyond routine chest computed tomography and bronchoscopy - Saurabh Mall; Rahul Kumar Sharma; Deepak Prajapat; Samir K Gupta; Deepak Talwar (Lung India, 2017)
Hemoptysis is considered as a medical emergency which requires urgent stabilization with identification and correction of underlying etiology. Diagnosis of the cause of hemoptysis is not always readily identified after bronchoscopy and conventional computed tomography (CT) chest. Arteriovenous malformation (AVM) is a rare but important cause of massive hemoptysis which can be easily picked up by the use of double turn contrast CT chest. We here report a rare congenital AVM anomaly called Klippel-Trenaunay-Parks-Weber syndrome as a cause of massive hemoptysis and utility of double turn CT in diagnosing AVM as a cause of hemoptysis.